Lipid Lowering Effect of Various Extracts of Whole Plant of Borreria hispida (Linn) in Rat Fed with High Fat Diet - Shaji Selvin, C.D.; Kottai Muthu, A. (Asian Journal of Chemistry, 2011)
The objective of the present investigation is to evaluate the lipid lowering effect of various extract of whole plant of Borreria hispida (Linn) in high fat fed rats. A total number of 36 animals were divided into 6 groups of six each. Group I normal, group II high fat diet, group IIIhigh fat diet plus pet. ether extract (200 mg/kg b.wt), group IV high fat diet plus ethyl acetate extract (200 mg/kg b.wt), group V high fat diet plus methanol extract (200 mg/kg b.wt), group VI high fat diet plus standard drug atorvastatin (1.2 mg/kg b.wt). Adminis-tration of high fat diet caused a significant rise (p < 0.001) in the plasma and tissues levels of total cholesterol, triglycerides, phospholipids, LDL-cholesterol, VLDL-cholesterol and total cholesterol: HDLcholesterol and LDL-cholesterol: HDL-cholesterol ratios. Simultaneous administration of various extract of Borreria hispida significantly reduces the plasma and tissues lipid and lipoprotein levels. The methanolic extract of Borreria hispida was found significantly decreased the levels of lipid and lipoprotein in plasma and tissues (liver, heart, aorta) than that of other extracts. It is concluded that the methanolic extract of Borreria hispida has potent lipid lowering effects in high fat fed rats.